Educational Planning in Context of Yakut, Kalmyk, and Karelian Languages - V. Yu. Mikhalchenko; E. A. Kondrashkina; S. V. Kirilenko (Научный диалог)
This article examines one component of language planning — educational planning. The main elements and indicators of this type of planning were identified. The authors discuss issues related to educational planning in three republics of the Russian Federation. The study was conducted based on the materials of the Kalmyk, Karelian, and Yakut languages. The aim of the research was to analyze educational planning as a set of existing opportunities for language learning. One of the objectives was to determine the scope and directions of activity in educational language planning. The second objective was to provide an overview of educational planning based on the materials of the Karelian, Kalmyk, and Yakut languages in synchrony and diachrony. The third objective was to analyze educational language planning according to our identified criteria and clarify the prestige of languages in the perception of speakers as a motivational factor for their study. To achieve this, the results of field research conducted in the three republics in 2021-2022 were analyzed. As a result of the study, it was concluded that the ethnic self-awareness of respondents is at a high level, and the symbolic significance of national languages is significant. However, there is a tendency towards a decrease in the number of individuals interested in studying their native (national) language in school education.